Sustaining fixed exchange rates : a model with debt and institutions - Pitt, Alexander; International Monetary Fund. African Department ([Washington, D.C.] : International Monetary Fund, African Dept., 2001)
Fixed exchange rate regimes have come into disrepute, as their defense has become all but impossible. Yet, while a determined attack on currency cannot be prevented or, ultimately, withstoods, policies can reduce the vulnerability of a country to such attacks.
Cover title.
"March 2001"--Page 1
Includes bibliographical references (pages 21-22).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Foreign exchange rates -- Developing countries -- Econometric models; Debts, External -- Developing countries -- Econometric models; Banks and banking -- Developing countries -- Econometric models; Developing countries -- Commercial policy -- Econometric models; Taux de change -- Pays en voie de développement -- Modèles économétriques.; Dettes extérieures -- Pays en voie de développement -- Modèles économétriques.; Banques -- Pays en voie de développement -- Modèles économétriques.; Pays en voie de développement -- Politique commerciale -- Modèles économétriques.; Banks and banking -- Econometric models; Commercial policy -- Econometric models; Debts, External -- Econometric models; Foreign exchange rates -- Econometric models; Developing countries; Electronic books